18F-fluorodeoxyglucose PET/CT findings in pleural effusions of patients with known cancer - Letovanec, I.; Allenbach, G.; Mihaescu, A.; Nicod Lalonde, M.; Schmidt, S.; Stupp, R.; Fitting, J.-W.; Boubaker, A.; Ris, H.-B.; Prior, J. O. (Nuklearmedizin - NuclearMedicine, 2012)
Aim: Pleural effusion is common in cancer patients and to determine its malignant origin is of huge clinical significance. PET/CT with 18F-FDG is of diagnostic value in staging and follow-up, but its ability to differentiate between malignant and benign effusions is not precisely known. Patients, methods: We examined 50 PET/CT from 47 patients (29 men, 18 women, 60 ± 16 years) with pleural effusion and known cancer (24 NSCLC, 7 lymphomas, 5 breasts, 4 GIST, 3 mesotheliomas, 2 head and neck, 2 malignant teratoma, 1 colorectal, 1 oesophageal, 1 melanoma) for FDG uptake in the effusions using SUVmax. This was correlated to cytopathology performed after a median of 21 days (interquartile range –3 to 23), which included pH, relative distribution (macrophages, neutrophils, eosinophils, basophils, lymphocytes, plasmocytes), and absolute cell count. Results: Malignant cells were found in 17 effusions (34%) (6 NSCLC, 5 lymphomas, 2 breasts, 2 mesotheliomas, 2 malignant teratomas). SUV in malignant effusions were higher than in benign ones [3.7 (95%CI 1.8–5.6) vs. 1.7 g/ml (1.5–1.9), p = 0.001], with a correlation between malignant effuUntersion and SUV (Spearman coefficient ρ = 0.50, p = 0.001), but not with other cytopathological or radiological parameters (ROC area 0.83 ± 0.06). Using a 2.2-mg/l SUV threshold, 12 PET/CT studies were positive and 38 negative with sensitivity, specificity, positive and negative predictive values of 53%, 91%, 75% and 79%, respectively. For NSCLC only (n = 24), ROC area was 0.95 ± 0.04, 7 studies were positive and 17 negative with a sensitivity, specificity, positive and negative predictive values of 83%, 89%, 71 and 94%, respectively. Conclusion: PET/CT may help to differentiate the malignant or benign origin of a pleural effusion with a high specificity in patients with known cancer, in particular NSCLC.
Keywords: Pleural effusion; tumour; PET/CT; FDG